PENGEMBANGAN MATERI PEMBELAJARAN COLLABORATIV LEARNING BERBASIS KEARIFAN LOKAL UNTUK MENGEMBANGKAN KARAKTER KREATIF DAN BERSAHABAT DI SD ISLAM KHAIRA UMMAH PADANG - Syofiani Syofiani (Program Studi PGSD FKIP Universitas Bung Hatta, 2020)
The article contains a discussion of the form of collaborative learning material based on local wisdom that can be used to develop creative and friendly character for students of SD Islam Khaira Ummah Padang. Respondents were fourth grade students of SD Islam Khaira Ummah Padang. Learning materials that can be used in an effort to develop a creative and friendly character, one of which is through a collaborative learning model based on local wisdom, in this case is Minangkabau local wisdom. The findings show that learning with a collaborative learning model based on local wisdom can make students have a creative and friendly character. It is indicated that students are able to create something new, not limited to things in the textbook. Meanwhile, the friendly character is also shown by students in collaborating with peers, causing an attitude of togetherness that does not win alone, so that no student feels isolated in the class